Performance assessment of municipal solid waste management for a city in England: past and future perspectives - Wang, Dan (2020)
Sustainable municipal solid waste (MSW) management is the key to achieve urban sustainability and circular economy via recycling materials and recovering energy from waste. It also contributes to mitigating global climate change and reducing impacts on human health and the environment. To combat the environmental impacts caused by MSW management, especially the impacts from landfills,EU Landfill Directive was introduced in 1999 to reduce the landfilled biodegradable municipal waste (BMW). After that, a series of waste directives have been put into enforcement to facilitate the establishment of sustainable MSW management in European countries. These waste directives initiated and drove the evolution of MSW management in the UK, but their realistic effects on the improvement of MSW management has not to date been investigated in detail. This study depicted the transition and assessed the performance of MSW management in Nottingham since the Waste Strategy 2000 published to respond to the EU Landfill Directive (throughout the period from April 2001 to March 2017)using the methods materials flow analysis (MFA) and life cycle assessment(LCA). To quantitatively estimate the potential energy that can be recovered from MSW, predictive models were built to estimate the lower heating value (LHV) of MSW using the two model building methods, multiple regression analysis and artificial neural network (ANN),based on 151 datasets which record the wet physical components of MSW and their measured LHV worldwide. Improvements in waste reduction, material recycling, energy recovery,and landfill prevention were observed in Nottingham because of the voluntary preventive actions and the introduction of new waste management strategies such as kerbside collection, material recovery facility (MRF) and production of residual derived fuel (RDF). MSW management in Nottingham transformed from a relatively simple model combining land filling and incineration with energy recovery to a more complex model integrating source separation, recycling, composting, pre-treating landfilled waste and incineration with energy recovery. During the period from 2001/02 to 2016/17, annual waste generation in Nottingham reduced from 463 kg/Ca to 361 kg/Ca, the recycling and composting share increased from 4.6% to 44.4%, and the landfill share reduced from 54.7% to 7.3%. These improvements resulted in a significant reduction of the greenhouse gas (GHG)emission from 1076.0kgCO2-eq./t of MSW (or 498.2kgCO2-eq./Ca) in 2001/02 to 211.3kgCO2-eq./t of MSW (or 76.3kgCO2-eq./Ca) in 2016/17. These signs of progress are believed to be driven by the EU waste directives and the associated policies and waste management targets established at both national and local levels. LHV predictive models generated using both methods (multiple regression analysis and ANN)exhibited acceptable and compatible levels of performance, based on the diagnostic tests on residuals (range and standard deviation), the standard error of the estimate(SEE) and mean absolute percentage error (MAPE). ANN models proved to be more robust in their handling of datasets of diverse quality. Models developed from both methods indicated a negative contribution of the wet food waste to LHV. Supported by the strong and significant correlation between food waste and moisture content, we concluded that the negative impact of the component with high moisture content on LHV outweighed its calorific value. This reveals that separating food waste or any other waste with high moisture content from the MSW to be incinerated can be the key to improved energy recovery efficiency. Based on the experience in analysing historical MSW management scenarios and building LHV predictive models, an alternative future scenario was proposed that assumed food waste and textile were separated at source,separately collected organic waste was treated using anaerobic digestion and residual waste was pre-treated in MRF before incineration.Based on the assessment using MFA and LCA, this future scenario could fulfil the high target to recycle 55% of household waste set by the local authority, and GHG emission from MSW management sector in Nottingham could be further reduced to as low as –142.3kgCO2-eq./t of MSW(or –40.2kgCO2-eq./Ca ). To realise this future scenario, enhanced source separation is especially important. Therefore, public education and supporting facilities on waste separation at the sources should be strengthened in the future.